Development of Islamic libraries: a Malaysian perspective - Balqis, Suja’ (Universiti Sains Islam Malaysia (USIM), 2010)
Organized by Islamic Science University of Malaysia (USIM) & Islamic International University of Malaysia (UIAM) in collaboration with Librarians Association of Malaysia (PPM) & Malaysia's Islamic Library Collection (KPIM), 25th - 27th November 2008 at Putra World Trade Center (PWTC), Kuala Lumpur. Link to publisher's homepage at http://www.usim.edu.my/